2016
DOI: 10.1007/s11655-016-2258-y
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative medicine therapies for chronic pain

Abstract: Pain afflflicts over 50 million people in the US, with 30.7% US adults suffering with chronic pain. Despite advances in therapies, many patients will continue to deal with ongoing symptoms that are not fully addressed by the best conventional medicine has to offer them. The patients frequently turn to therapies outside the usual purview of conventional medicine (herbs, acupuncture, meditation, etc.) called complementary and alternative medicine (CAM). Academic and governmental groups are also starting to incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 78 publications
1
39
0
3
Order By: Relevance
“…23 Additional articles on EO use in BPSD 42,46,47 and cognitive function 48,49 showed positive results, but were not reviewed, as they did not meet inclusion criteria due to study type, sample size, or applicability of the outcome variables. Other reviews that might be helpful resources for additional CAM options, are Bauer’s CAM in chronic pain 22 and Wardell’s review on healing touch, 27 as well as a large review showing that music therapy and behavioral management techniques were effective for BPSD. 45 Traditional Chinese Medicine (TCM) was not included in this review, but is widely used in Asia 50,51 and has several compelling studies looking at cognitive function in dementia, 52,53 as well as on BPSD and ADLs in dementia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Additional articles on EO use in BPSD 42,46,47 and cognitive function 48,49 showed positive results, but were not reviewed, as they did not meet inclusion criteria due to study type, sample size, or applicability of the outcome variables. Other reviews that might be helpful resources for additional CAM options, are Bauer’s CAM in chronic pain 22 and Wardell’s review on healing touch, 27 as well as a large review showing that music therapy and behavioral management techniques were effective for BPSD. 45 Traditional Chinese Medicine (TCM) was not included in this review, but is widely used in Asia 50,51 and has several compelling studies looking at cognitive function in dementia, 52,53 as well as on BPSD and ADLs in dementia.…”
Section: Discussionmentioning
confidence: 99%
“…17 Medications, such as anti-psychotics, are often overused and have significant adverse events in the dementia population. 18 Complementary and Alternative Medicine (CAM) may offer a less invasive, safer, and more gentle option to treat BPSD, 1921 as well as pain, 19,20,22 and improve quality of life. 20,23,24 Reducing BPSD may also reduce the burden on the critical care nurse and support staff.…”
Section: Introductionmentioning
confidence: 99%
“…are commonly used, but limited in the efficacy due to adverse effects as tolerance and addiction. Increasing evidence has shown that acupuncture therapy has a positive role in relieving chronic pain, and many patients ask for acupuncture treatment [ 21 , 22 ]. Our past studies demonstrated that repeated EA intervention could relieve neuropahtic pain in CCI rats, which was closely related with its effects in regulating activities of the cholinergic system and the ERK signal pathway in the hippocampus and hypothalamus [ 23 , 24 ], as well as in upregulating the expression of IL-1β mRNA, TNF-α mRNA, IL-6 mRNA, and BDNF, NGF, and NT3/4 in the spinal cord [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…14 Women access CAM services more often than men, [15][16][17] and pain is a leading motive for patients to seek CAM. 18 Specifically, women also report using CAM more often than men for headaches and migraines, and preventative services. 17,19 Among the U.S. cancer population, women are significantly more likely to use CAM, particularly for pain, depression, and insomnia.…”
Section: Introductionmentioning
confidence: 99%